Employees Feeling Respect as a Chosen Predictor of Involvement in the Organisational - Szczygieł, Alicja (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Current management of human capital is not limited to the motivation of workers to perform their duties. Companies strive to build capital with employees who are both motivated and involved in the organisation. A high level of commitment obviously brings organisations numerous benefits, and although the issue has been discussed for years, it remains a source of scientific interest and business. Involved employees are loyal to their companies beyond the scope of their duties, and act upon their own initiative, often contributing to improved organisational efficiency. The article pays particular attention to the need for employees to feel respect from supervisors and its importance for affective, normative and lasting engagement.